Pengaruh self efficacy terhadap kemampuan literasi matematis pada materi transformasi geometri siswa kelas IX SMP N 1 Linggo Sari Baganti - Okviani Syafti; Yanti Nasmai Ekaputri; Vira Syaprianti (Algebra: Journal of Matematics, Statistics and Computation, 2025)
Mathematical literacy is an essential competence in mathematics learning because it requires students to formulate, use, and interpret mathematical concepts in various real-life contexts. However, international studies indicate that Indonesian students’ mathematical literacy remains relatively low. One factor presumed to influence this ability is self-efficacy, namely students’ belief in their own ability to complete tasks. This study aimed to analyze the effect of self-efficacy on mathematical literacy skills in the topic of geometric transformations among ninth-grade students at SMP Negeri 1 Linggo Sari Baganti. This research employed a quantitative approach with a causal associative design using an ex post facto method. The research subjects were 30 students from class IX.4 selected through purposive sampling. Data were collected using a self-efficacy questionnaire and a mathematical literacy test in the form of contextual essay questions. Data analysis was conducted using normality and linearity tests, Product Moment correlation, and simple linear regression. The results showed that there was a positive and significant effect of self-efficacy on students’ mathematical literacy skills. Students with higher self-efficacy tended to demonstrate better ability in modeling problems, applying geometric transformation concepts, and interpreting solution results. These findings imply that improving students’ self-efficacy should be a concern in mathematics learning in order to support the enhancement of their mathematical literacy skills.